Elucidating the formation of terra fuscas using Sr–Nd–Pb isotopes and rare earth elements. (March 2015) - Hissler, Christophe; Stille, Peter; Juilleret, Jérôme; Iffly, Jean François; Perrone, Thierry; Morvan, Gilles
Highlights: Geochemical evidences on stabile phase confirm Bajocian marl as terra fusca parent material. Precipitation/Dissolution of secondary carbonates controls geochemistry of labile phases. This terra fusca sequence record at least four geological and environmental events. Abstract: Carbonate weathering mantles, like terra fusca, are common in Europe but their formation and evolution is still badly understood. We propose to combine geological, mineralogical and pedological knowledge with trace element and isotope data of a weathering mantle as a novel approach to understand the evolution of terra fuscas . Sr–Nd–Pb isotopes and rare earth element (REE) contents were analyzed in a cambisol developing on a typical terra fusca on top of a condensed Bajocian limestone-marl succession from the eastern side of the Paris Basin. The isotope data, REE distribution patterns and mass balance calculations suggest that the cambisol mirrors the trace element enrichments present in this carbonate lithology, which are exceptionally high compared to global average carbonate. The deeper soil horizons are strongly enriched not only in REE (ΣREE: 2640 ppm) but also in redox-sensitive elements such as Fe (44 wt.%), V (1000 ppm), Cr (700 ppm), Zn (550 ppm), As (260 ppm), Co (45 ppm) and Cd (2.4 ppm). The trace element distribution patterns of the carbonate bedrock are similar to those of the soil suggesting their close genetic relationships. Sr–Nd–Pb isotope data allow to identify four principal components in the soil: a silicate-rich pool close to the surface, a leachable REE enriched pool at the bottom of the soil profile, the limestone on which the weathering profile developed and an anthropogenic, atmosphere-derived component detected in the soil leachates of the uppermost soil horizon. The leachable phases are mainly secondary carbonate-bearing REE phases such as bastnaesite ((X) Ca(CO3 )2 F) (for X: Ce, La and Nd). The isotope data and trace element distribution patterns indicate that at least four geological and environmental events impacted the chemical and isotopical compositions of the soil system: 1. An oxygen-deficient diagenetic or hydrothermal event caused trace metal enrichments in the Bajocian limestone-marls. 2. Carbonate dissolution caused the enrichment of detrital silicate phases and authigenic REE-bearing residual phases – e.g. marine authigenic fluorapatites and bastnaesite – in the newly formed condensed horizons. 3. Dissolution/precipitation of metastable bastnaesite phases and downward migration of the REE during soil formation. 4. Overprinting of the chemical and isotopical compositions of the uppermost soil horizon by recent atmospheric depositions.